Evaluation of the psychometric properties of the Oral Health Behavior Social Support (OHBSS) Scales in English and Spanish for Mexican-origin young adults - Tracy L. Finlayson; Cristian Garcia-Alcaraz; Vanessa L. Malcarne; Mark Ryder; Guadalupe X. Ayala; Lourdes S. Martinez; Melody K. Schiaffino; Kristin S. Hoeft; Stuart A. Gansky; Erin Dougherty; Nannette Stamm; Brian Shue; et al. (BMC Oral Health)
Abstract Background Valid, reliable measures of psychosocial constructs are needed in oral health research. This study quantitatively evaluated the psychometric properties of nine new Oral Health Behavior Social Support (OHBSS) scales, which measured support for three oral health behaviors (brushing, flossing, dental care), queried for each of three sources (family, health providers, others/friends). Methods Young Mexican-origin adults in the southwestern United States-Mexico border region completed an online survey, in English or Spanish (N = 502). Survey items included: OHBSS scales, general social support scales, oral health behaviors, self-rated oral health status, dental anxiety, acculturation and socio-demographics. Subsample 1 participants also completed a dental exam (N = 41). Subsample 2 participants also completed a repeat OHBSS survey two-to-six weeks later (N = 56). Psychometric properties were tabulated, overall and by language preference (English or Spanish). Convergent and divergent validity were evaluated via correlations between the dental-specific OHBSS social support scales, scores from three validated general social support scales, and scales expected to be largely unrelated (acculturation, dental anxiety). Correlations examined predictive validity between the OHBSS scales and oral health behaviors, and self-reported and clinical outcomes. Test–retest reliability was assessed via intraclass correlation coefficients in Subsample 2. Results Of 502 participants, 60% preferred speaking English, 37% were single, and 21% were male. OHBSS scores indicated that health providers then family provided the most support for all three oral health behaviors, while others/friends did not provide much support. Spanish speakers tended to have higher OHBSS scores than English speakers. Correlations followed expected patterns and supported convergent and divergent validity, in the full sample and across languages. OHBSS scales exhibited many significant weak-moderate positive correlations (r = 0.10–0.38) with general social support scales. Few (11/108) significant correlations (< -0.16) were observed between OHBSS scales, acculturation, and dental anxiety. OHBSS scales exhibited some significant weak-moderate positive correlations with oral health-promoting behaviors. OHBSS scales were not associated with clinical outcomes. OHBSS scales exhibited good test–retest reliability overall and in Spanish. Conclusion Psychometric properties for the OHBSS scales were acceptable in both English and Spanish versions. The scales are valid and reliable tools for assessing social support for oral health-promoting behaviors from family, health providers, and others/friends. Trial registration Not applicable.